Peranan Lembaga Adat Dalam Penyelesaian Delik Adat Pada Masyarakat Di Desa Toruakat Kecamatan Dumoga Kabupaten Bolaangmongondow - Cindai Goni; Fenty Puluhulawa; Jufryanto Puluhulawa (Hakim, 2024)
The aim of this research is to find out the form of customary law that is resolved in customary justice in the Deisa Toiruakat community, Dumoiga subdistrict, Boilaang Moingoindoiw district and to find out the legal process of customary law in Deisa Toiruakat, Dumoiga subdistrict, Boilaang Moingoindoiw district. The Meitoidei Peineilitian that is used is a combined type of research between Noirmative Huikuim Peineilitian and Eimpirical Huikuim Peineilitian. Noirmative-Eimpirical Huikuim Research is a type of research theory which in this case combines noirmative legal science which is coincided with the addition of data or empirical science. The research results obtained by the customary settlement process in Toruakat Village do not violate existing legal norms in Indonesia because the Guhanga Lipu (Traditional Institution) of Toruakat Village and customary courts are recognized by the Government both through laws, regional regulations and village regulations. The conclusion is that there are differences between the traditional regulations of Toruakat Village and the practice of carrying out customary trials that are carried out, because the sound of the articles mentioned in the trial process is different from the sound of the articles in Toruakat Village Regulation Number: 01 of 2020 Concerning the Customary and Customary Procedures of Toruakat Village and the number of sanctions imposed This also differs from the provisions for giving sanctions in the village regulations and in the research process the researcher found that indeed the traditional council did not comply with the traditional village regulations of Toruakat Village, they only relied on knowledge from their parents and from books that their ancestors had left to them.